2008
DOI: 10.1038/sj.bjc.6604753
|View full text |Cite
|
Sign up to set email alerts
|

FTIR-based spectroscopic analysis in the identification of clinically aggressive prostate cancer

Abstract: Fourier transform infrared (FTIR) spectroscopy is a vibrational spectroscopic technique that uses infrared radiation to vibrate molecular bonds within the sample that absorbs it. As different samples contain different molecular bonds or different configurations of molecular bonds, FTIR allows us to obtain chemical information on molecules within the sample. Fourier transform infrared microspectroscopy in conjunction with a principal component-discriminant function analysis (PC-DFA) algorithm was applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
139
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(142 citation statements)
references
References 20 publications
2
139
0
1
Order By: Relevance
“…Figure 2 shows the spectrum of the dried complete serum sample (A), the >100K serum fraction (B), and the <100Kserum fraction (D). Table 1 provides a list of band assignments [41][42][43][44][45][46][47] . Although the >100K serum fraction is very similar to that of the pure serum, consistent with the >100K fraction containing the most abundant proteins, the spectral profile of the 100K-10K fraction is significantly different, supporting the fractionation approach to provide more diagnostic information.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the spectrum of the dried complete serum sample (A), the >100K serum fraction (B), and the <100Kserum fraction (D). Table 1 provides a list of band assignments [41][42][43][44][45][46][47] . Although the >100K serum fraction is very similar to that of the pure serum, consistent with the >100K fraction containing the most abundant proteins, the spectral profile of the 100K-10K fraction is significantly different, supporting the fractionation approach to provide more diagnostic information.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research has shown that FTIR spectroscopy coupled with multivariate analysis is a promising means of reinforcing the Gleason scoring system of grading prostate cancer [24][25][26][27]. FTIR spectra from CaP tissue biopsy samples were analysed using linear discriminant analysis (LDA) to construct a grading model.…”
Section: Biophotonicsmentioning
confidence: 99%
“…The higher signal levels achievable with FTIRM result in increased speed of measurement and consequently higher sample throughput over CRM [21]. The strengths of both are now well established in hyperspectral imaging for non-invasive and label-free histopathology [22][23][24][25][26][27][28][29][30], while the capabilities of CRM to detect tissue abnormalities in-vivo without the complication of contamination of spectral measurements by water and atmospheric features has resulted in a move to the development of clinical devices [31].…”
Section: Introductionmentioning
confidence: 99%